A longitudinal study of the moderating effects of romantic relationships on the associations between alcohol use and trauma in college students. (22nd April 2021) - Smith, Rebecca L.; Dick, Danielle M.; Amstadter, Ananda; Thomas, Nathaniel; ,; Salvatore, Jessica E.
Abstract: Background and Aims: College students report high levels of alcohol use, which can be exacerbated by interpersonal trauma exposure (IPT). Romantic relationships may represent salient contexts for moderating associations between IPT and alcohol use. We examined whether relationship status, partner alcohol use and relationship satisfaction moderated associations between IPT and alcohol use, and whether these associations varied in a sex‐specific manner. Design: University‐wide longitudinal survey of college students. Setting: Large, urban public university in mid‐Atlantic United States. Participants: We used two subsets of participants ( n = 5673 and 3195) from the Spit for Science project, a longitudinal study of college students. Participants completed baseline assessments during the autumn of their freshman year and were invited to complete follow‐up assessments every spring thereafter. Participants were included in the present study if they completed surveys at baseline and at least one follow‐up assessment (meanfollow‐ups = 1.70, range = 1–4). Measurements: Predictors included precollege and college‐onset IPT, relationship status, partner alcohol use, relationship satisfaction and sex. Alcohol consumption was the primary outcome of interest. Pre‐college IPT was measured at baseline and all other measures were assessed at each follow‐up. Findings: Individuals with pre‐college IPT consumed more alcohol than those without IPT, but this was mitigated for those in relationships (β = −0.15, P = 0.046, 95% confidence interval (CI) = −0.29, 0.00). Individuals with college‐onset IPT consumed more alcohol than those without IPT, and this was more pronounced for those with higher partner alcohol use (β = −0.18, P = 0.001, 95% CI = −0.29, −0.07). Relationship satisfaction was not a significant moderator of the associations between IPT and alcohol use ( P s > 0.05 and 95% CIs include 0). Conclusions: Involvement in relationships, but not relationship satisfaction, appears to reduce the effects of interpersonal trauma exposure (IPT) on alcohol use among US college students, while high partner alcohol use appears to exacerbate it. The moderating effects of relationship characteristics depend on the developmental timing of IPT.